Berruyer's Bible: public opinion and the politics of Enlightenment Catholicism in France - Watkins, Daniel J. (McGill-Queen's studies in the history of religion, 2021)
French Jesuits and the Enlightenment -- The Problem of Innovation -- The Berruyer Affair -- From Ink to Ashes -- The Suppression -- A Bible for a Post-Revolutionary Age -- Conclusion: From Enlightenment to Romantic Catholicism